A Health Systems Strengthening Approach to Female Genital Fistula in Kenya - Wala, Elizabeth; Mwoka, Meggie; Okoro, Dan (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To contribute to Universal Health Coverage by strengthening the capacity of the health system in Kenya to address female genital fistula using NHIF as an entry point. Methods: This involves a revolving fund model using NHIF rebates from an initial donor funded payment of NHIF premiums for 3 years for as part of FGF management. USD 180 will be paid for NHIF subscription per patient. This will cover the woman and her dependents for 3 years. NHIF in return will pay a rebate of USD 600 per patient. The rebates will be used by County Governments for facility improvement especially on reproductive health services. This will be done with support from UNFPA who will provide technical guidance, capacity building, support of repair services and resource materials. Results: The expected results of this innovative approach include: Contribution to Universal Health Coverage through increased uptake of NHIF; increased knowledge of health workers on RMNCH and FGF management; insurance cover for fistula champion and her dependents; and strengthening policies and legislation around facility improvement funds. Conclusions: Addressing FGF will require a concentrated and coordinated effort at the national and local levels of different stakeholders under the leadership of the Ministry of Health (MOH) and county government to provide centralized coordination to ensure that quality services are available. Using NHIF as an entry point, the domino effect is health systems strengthening around FGF management and social health protection for household. This is a shift from the previous patient-focused management of fistula that had individual and not social impact.